Risk Based Capital Sebagai Tolok Ukur Kinerja Keuangan Perusahaan Asuransi Jiwa Dalam Membantu Masyarakat Yang Hendak Berasuransi - I Nyoman Winata; Mulawarman Awaloedin (AKUNTANSI 45, 2023)
The purpose of this study is to analyze the difference in the RBC between the national life insurance company and the joint venture life insurance company and to analyze the impact of the difference in the RBC for people who want to be insured. The method used is a case study on national life insurance companies and joint life insurance companies, each with 5 companies with the largest assets, in 2019-2020. While the type of data is secondary data collected through the website of each company in the form of financial statements. The analysis technique was carried out by means of a different mean test (Compare Means) or a t-test (t-test) with the help of SPSS. Then analyze the impact of differences in the RBC achievement for people who want to be insured. The calculation results show that there is no difference in the RBC between the national life insurance company and the joint venture life insurance company. However, judging from the average RBC, national life insurance companies have not shown better financial performance than joint venture life insurance companies. This has an impact on the lack of public trust in national life insurance companies, which has the potential to cause the company's inability to cope with the risk of future losses.